Prevalence of Excessive Tearing in Women With Early Breast Cancer Receiving Adjuvant Docetaxel-Based Chemotherapy - Chan, Arlene; Su, Charles; De Boer, Richard; Gajdatsy, Adam (American Society of Clinical Oncology, 2013)
Purpose: To define the incidence and impact of tearing in patients receiving adjuvant docetaxel-based chemotherapy and assess for lacrimal duct obstruction (LDO) as a causative factor. Patients and Methods: Consecutive patients with early breast cancer recommended for docetaxel-based chemotherapy with no prior ocular symptoms were included. Before and after completion of chemotherapy, patients underwent lacrimal drainage evaluation by computed tomographic dacrocystography (CT-DCG) and ophthalmic assessment. Eye symptoms were assessed at baseline, during, and after completion of chemotherapy. Results: Over a 22-month period, 100 patients were recruited. Asymptomatic LDO was present at baseline in 17% and 18% of patients, as assessed by ophthalmic review and CT-DCG, respectively. Overall, 86% of patients developed tearing, with no significant difference between those who did and did not have LDO (94% v 84%; P = .45). Blepharitis occurred in 37% and minor corneal epitheliopathy in 22% of patients, with neither condition predicting for the development of tearing. Impairment of visual activities was greatest after cycle one (70% of patients) but had decreased to < 5% by 4 months after treatment. Conclusion: Tearing occurs in the majority of patients receiving adjuvant docetaxel-based chemotherapy regimens and occurred similarly in patients with and without LDO. There was poor concordance between CT-DCG and ophthalmic examination in the detection of LDO. Tearing and other eye symptoms impaired visual activities, but in nearly all patients, both symptoms and functional impairment were mild and had resolved by 4 months after chemotherapy. Our study demonstrates docetaxel-related tearing is not caused by LDO, and as such, evaluation or stenting of the duct is not considered necessary.